2020
DOI: 10.3390/molecules25163764
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kerogen Thermal Maturity on Methane Adsorption Capacity: A Molecular Modeling Approach

Abstract: The presence of kerogen in source rocks gives rise to a plethora of potential gas storage mechanisms. Proper estimation of the gas reserve requires knowledge of the quantities of free and adsorbed gas in rock pores and kerogen. Traditional methods of reserve estimation such as the volumetric and material balance approaches are insufficient because they do not consider both the free and adsorbed gas compartments present in kerogens. Modified versions of these equations are based on adding terms to account for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 34 publications
6
21
0
Order By: Relevance
“…In addition, the CH 4 adsorption capacity increases with thermal maturity in Type II kerogen series. These results match those observed in earlier modeling studies [43][44][45]49,53 and experimental measurements. 82−86 The CH 4 adsorption capacity was found to be the highest in Type II-D kerogens compared to the other kerogen types.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the CH 4 adsorption capacity increases with thermal maturity in Type II kerogen series. These results match those observed in earlier modeling studies [43][44][45]49,53 and experimental measurements. 82−86 The CH 4 adsorption capacity was found to be the highest in Type II-D kerogens compared to the other kerogen types.…”
Section: Resultssupporting
confidence: 92%
“…In both studies, a positive correlation has been shown between methane adsorption and kerogen maturity. This is further supported by a later study by Alafnan et al Tesson and Firoozabadi reported methane adsorption in both rigid and flexible Type II-A kerogens and concluded that kerogen flexibility has a limited effect on the self-diffusion of methane. It is worth pointing out that while ensuring flexibility of the kerogen matrix, their MD simulations were conducted in the NVT ensemble, where deformation was not accounted for.…”
Section: Introductionsupporting
confidence: 59%
“…The convergence in the density is consistent with estimated mechanical moduli as shown in Figure 8. Similar observations of the number of units needed to form a realistic kerogen structure are reported in the literature [79][80][81][82][83][84].…”
Section: Resultssupporting
confidence: 84%
“…Moreover, the storage capacity is highly influenced by the origin and the maturation of organic matter. The adsorption capacity positively correlates with maturation as reported by different studies [20][21][22].…”
Section: Gas Accumulationsupporting
confidence: 64%